Rural areas and territorial governance : the case of the Portuguese municipality of Almeida - Fonseca, Fernando Pereira da (2008)
Rural development is a multidimensional process. To be successful, the development strategies in rura areas should be supported in appropriate governance patterns in order to stimulate the dialog and the cooperation between public and private entities. In fact, local governance is often a key factor of rural development, allowing the integration of objectives and policies, establishing relations of power distribution, and defining resources accountability, priorities and choices. Thus, territorial governance reflects the local capacity of involvement and cooperation in the development process, the degree of organisational innovation to surpass internal debilities and the external concurrence. Consequently, territorial governance configures a sustainable perspective of developmen and takes important territorial core values such as coherence and diversity in areas under pressure, such as the periphera rural areas. This paper aims at analysing a particular and paradigmatic Portuguese rural and peripheral territory, the municipality of Almeida that is living a trend of socio-economic decline. Anchored on a research developed in thi territory, the paper attempts to examine the characteristics and reasons of the present governance structure, its reflexes in the local (sub)development, and the opinion and position of some influent entities in a context of a new governance Furthermore, the paper explores and highlights the benefits and constraints that emerge when governance i contextualised in rural territories, once it poses several questions and challenges to the local capacity of institutiona articulation. Due to the same nature of the problems involved, the main conclusions obtained could be extrapolated to much more rural and peripheral territories.